Social media as health educator: An assessment of the understandability and accuracy of tiktok content about contraception - Julianna K. Coleman; Maetal E. Haas-Kogan; Andrea Pelletier; Rachel E. Stoddard; Natasha R. Johnson; Julia R. Beatini; Nora Y. Sun; Alex S. Keuroghlian; Deborah Bartz (Contraception and Reproductive Medicine)
Abstract Background Contraception knowledge and attitudes are largely formed from conversations within one’s social network. More recently, this network has expanded to include social media. As the fastest growing social media platform, we aimed to assess popular contraception videos on TikTok for content understandability, actionability and accuracy. Methods This is a secondary analysis of the most viewed, contraception-specific TikTok videos that were previously coded as containing educational messaging in a content-analysis study. We assessed videos for understandability (ability to explain a key message) and actionability (identify what they can do to act on that message) using the Patient Education Materials Assessment Tool for Audiovisual Materials (PEMAT-A/V) instrument and for Currency, Relevance, Authority, Accuracy, and Purpose (CRAAP) using a modified instrument within the health information education literature. Results The 174 videos with educational content scored as understandable but not actionable in PEMAT-A/V assessment, with videos created by healthcare providers (HCPs) performing better than those by non-HCPs in six of eleven domains of understandability. Videos overall scored well in relevance and purpose within the CRAAP assessment. Videos created by HCP’s (n = 99) scored higher than those by non-HCPs (n = 75) in relevance (score = 3.9 versus 3.3), authority (score = 4.8 versus 1.7), accuracy (score = 6.0 versus 3.5), and purpose (score = 7.1 versus 5.7) [all p < 0.001]. Regarding video engagement, the median number of views among the videos in the cohort was 604,450. Of all video views, 79.2% were of HCP-created videos and 20.8% were of non-HCP videos. Discussion Much of the contraceptive educational messaging on TikTok is understandable, relevant, and accurate. HCP-created videos overall scored better as compared to other creators, though even HCP-created videos score fail to provide actionable recommendations. The videos created by HCP also had greater metrics of engagement. Given this, we encourage HCPs to use social media to better inform its users.